Insect immunity. A transgenic analysis in Drosophila defines several functional domains in the diptericin promoter. - Meister, M (1994)
Diptericins are antibacterial polypeptides which are strongly induced in the fat body and blood cells of dipteran insects in response to septic injury. The promoter of the single-copy, intronless diptericin gene of Drosophila contains several nucleotide sequences homologous to mammalian cis-regulatory motifs involved in the control of acute phase response genes. Extending our previous studies on the expression of the diptericin gene, we now report a quantitative analysis of the contribution of various putative regulatory elements to the bacterial inducibility of this gene, based on the generation of 60 transgenic fly lines carrying different elements fused to a reporter gene. Our data definitively identify two Kappa B-related motifs in the proximal promoter as the sites conferring inducibility and tissue-specific expression to the diptericin gene. These motifs alone, however, mediate only minimal levels of expression. Additional proximal regulatory elements are necessary to attain some 20% of the full response and we suspect a role for sequences homologous to mammalian IL6 response elements and interferon-gamma responsive sites in this up-regulation. The transgenic experiments also reveal the existence of a distal regulatory element located upstream of -0.6 kb which increases the level of expression by a factor of five.